2014
DOI: 10.1007/s00299-014-1661-0
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping and candidate gene analysis of a major QTL for panicle structure in rice

Abstract: Key messageA gene not only control tiller and plant height, but also regulate panicle structure by QTL dissection in rice.AbstractAn ideal panicle structure is important for improvement of plant architecture and rice yield. In this study, using recombinant inbred lines (RILs) of PA64s and 93-11, we identified a quantitative trait locus (QTL), designated qPPB3 for primary panicle branch number. With a BC3F2 population derived from a backcross between a resequenced RIL carrying PA64s allele and 93-11, qPPB3 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
0
21
0
2
Order By: Relevance
“…For instance, D88 and WSL preferred the intronic poly(A) sites in indica but 3′ UTR sites in japonica (Figure a, Table S7). D88, encoding a putative esterase, negatively regulates tiller number, rice shoot branching and panicle structure via the strigolactone signal transduction pathway (Gao et al ., ; Peng et al ., ; Zhao et al ., ). WSL is characterized as a nuclear‐encoded plastid RNA splicing factor that affects chloroplast development and responds to ABA, sugar and salinity stresses by regulating the splicing of chloroplast transcript rpl2 (Tan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, D88 and WSL preferred the intronic poly(A) sites in indica but 3′ UTR sites in japonica (Figure a, Table S7). D88, encoding a putative esterase, negatively regulates tiller number, rice shoot branching and panicle structure via the strigolactone signal transduction pathway (Gao et al ., ; Peng et al ., ; Zhao et al ., ). WSL is characterized as a nuclear‐encoded plastid RNA splicing factor that affects chloroplast development and responds to ABA, sugar and salinity stresses by regulating the splicing of chloroplast transcript rpl2 (Tan et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Telah dilaporkan gen Dwarf 88 (D88)/Dwarf 14 (D14) mengatur tinggi tanaman dan jumlah anakan. Namun, gen D88/D14 tidak hanya mengatur anakan, tetapi juga mempengaruhi struktur malai (Peng et al, 2014). Gen MONOCULM 1 (MOC1) merupakan gen yang penting dalam mengontrol anakan padi.…”
Section: Heritabilitas Karakter Malaiunclassified
“…The mean panicle length for Indonesian rice landraces was 24.1, in which Ketan Mayang had the longest panicle length (35.7 cm). Peng et al (2014) reported that panicle structure is one of the most important factors for rice yield and panicle branches and their number affects spikelet number. Dense panicle structure has been a major target for improvement of rice grain yield because of its relationship with grain number.…”
Section: Agro-morphological Characteristicmentioning
confidence: 99%